The impact of expressive flexibility and self-control on moral competence following exposure to simulated combat-like environments in 18-22-year-old U.S. Military Recruits - Vasiliki Georgoulas-Sherry (Universitas Negeri Padang, 2022)
The impact on moral competence following exposure to combat-like environments can be found in soldier narratives, however, limited scientific research investigates such effects. Moreover, the influence of one's expressive flexibility and self-control on moral competence following combat-like environments is unknown. Employing a univariate design, this study recruited 107 participants (i.e., ages 18 to 22) from a private U.S. Military university to examine the impact on moral competence, including potential moderating effects of expressive flexibility and self-control, following exposure to combat-like environments. To simulate a combat-like environments, participants were placed in either immersive (i.e., Bravemind) or non-immersive (i.e., Virtual Battlespace 3) virtual environments. Self-reported expressive flexibility, self-control, and moral competence were assessed. Results revealed that following exposure to combat-like environments, an individual's moral competence increased. A main effect of self-control on moral competence indicated that an individual's self-control directly effects an individual's moral competence. Findings from this study offers a richer comprehension of how, following simulated combat environments, moral competence can be influenced, and how expressive flexibility and self-control can aid in protecting mental health and wellbeing, even in judging moral dilemmas.